2005
DOI: 10.1105/tpc.105.037713
|View full text |Cite
|
Sign up to set email alerts
|

A Rice Glutamate Receptor–Like Gene Is Critical for the Division and Survival of Individual Cells in the Root Apical Meristem

Abstract: Glu receptors are known to function as Glu-activated ion channels that mediate mostly excitatory neurotransmission in animals. Glu receptor–like genes have also been reported in higher plants, although their function is largely unknown. We have identified a rice (Oryza sativa) Glu receptor–like gene, designated GLR3.1, in which mutation by T-DNA insertion caused a short-root mutant phenotype. Histology and DNA synthesis analyses revealed that the mutant root meristematic activity is distorted and is accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(134 citation statements)
references
References 46 publications
(55 reference statements)
3
130
1
Order By: Relevance
“…However, there exist in Arabidopsis at least 44 genes encoding aminotransferases (Liepman and Olsen, 2004) that could be potential targets for AVG or other PLP inhibitors. Likewise, recent studies in Arabidopsis reported that L-Glu modulates both mitotic activity in the apical meristem (Li et al, 2006;Walch-Liu et al, 2006) and dynamic elongation of root cell files via the microtubule cytoskeleton (Sivaguru et al, 2003). The very surprising point of our results is that, in our hands, L-Glu root treatment in the presence of AVG displayed an increase in root elongation and presented exactly the opposite root phenotype that has been reported in plants treated with L-Glu alone (Sivaguru et al, 2003;Walch-Liu et al, 2006).…”
Section: Does Glu Issued From N Metabolism Act On Root Elongation Comcontrasting
confidence: 50%
“…However, there exist in Arabidopsis at least 44 genes encoding aminotransferases (Liepman and Olsen, 2004) that could be potential targets for AVG or other PLP inhibitors. Likewise, recent studies in Arabidopsis reported that L-Glu modulates both mitotic activity in the apical meristem (Li et al, 2006;Walch-Liu et al, 2006) and dynamic elongation of root cell files via the microtubule cytoskeleton (Sivaguru et al, 2003). The very surprising point of our results is that, in our hands, L-Glu root treatment in the presence of AVG displayed an increase in root elongation and presented exactly the opposite root phenotype that has been reported in plants treated with L-Glu alone (Sivaguru et al, 2003;Walch-Liu et al, 2006).…”
Section: Does Glu Issued From N Metabolism Act On Root Elongation Comcontrasting
confidence: 50%
“…Overexpression of another GLR, At GLR3.1, impaired long-term stomatal closure but did not affect the short-term stomatal closure response or the kinetics of Ca 2+ oscillations that were imposed by extracellular Ca 2+ . In rice (Oryza sativa), disruption of the Os GLR3.1 gene results in reduced growth of the primary root and of adventious roots especially in the early seedling stage due to reduced mitotic activity of the root apical meristem (Li et al, 2006a). GLRs also have been implicated in root development in Arabidopsis since Glu can affect root architecture (Walch-Liu et al, 2006).…”
Section: Ligand-gated Channels At the Plasma Membranementioning
confidence: 99%
“…These roles include regulation of hypocotyl elongation (Lam et al, 1998;Dubos et al, 2003), sensing of mineral nutrient status (Kim et al, 2001), regulating carbon/nitrogen balance (Kang and Turano, 2003), resisting aluminum toxicity (Sivaguru et al, 2003) and cold (Meyerhoff et al, 2005), root meristem function (Li et al, 2006;Walch-Liu et al, 2006), as well as jasmonate-mediated defense mechanisms (Kang et al, 2006).…”
mentioning
confidence: 99%